Ab initio electron scattering cross-sections and transport in liquid xenon. (2nd August 2016) - Boyle, G J; McEachran, R P; Cocks, D G; Brunger, M J; Buckman, S J; Dujko, S; White, R D
Abstract: Ab initio fully differential cross-sections for electron scattering in liquid xenon are developed from a solution of the Dirac–Fock scattering equations, using a recently developed framework (Boyle et al 2015 J. Chem. Phys .142 154507) which considers multipole polarizabilities, a non-local treatment of exchange, and screening and coherent scattering effects. A multi-term solution of Boltzmann's equation accounting for the full anisotropic nature of the differential cross-section is used to calculate transport properties of excess electrons in liquid xenon. The results were found to agree to within 25% of the measured mobilities and characteristic energies over the reduced field range of 10 −4 –1 Td. The accuracies are comparable to those achieved in the gas phase. A simple model, informed by highly accurate gas-phase cross-sections, is presented to improve the liquid cross-sections, which was found to enhance the accuracy of the transport coefficient calculations.